Risk factors for lower extremity injuries in young badminton players - Kang, Ang Lin; Ramalingam, Vinodhkumar (2018)
AIMS: Based on the limited evidence available about the intrinsic factors causing lower extremity injuries among Malaysian badminton players, this study was aimed to determine the relationship of demographic and physical characteristics to lower extremity injuries in young badminton players. METHODS: A cross-sectional study included badminton players between 14 and 24 years of age, categorized into case and control groups. Participants diagnosed with lower limb injuries were designated as cases, and those with no reported injuries were designated as controls. Personal information including demographic data, level of athlete and injury history was collected using a questionnaire. Independent t-test was used to analyze the differences between intrinsic characteristics in cases and controls. Pearson's χ2 was applied to evaluate the association between risk factors and general lower limb injuries, knee injuries and ankle injuries, with 95% confidence interval (CI). A p value of ≤0.05 was considered significant. RESULTS: A total of 106 young badminton players (83 males, 23 females) were recruited, of whom 42 participants were allocated as the case group, and 64 participants were allocated as the control group. A total of 60 lower extremity injuries were reported among the 42 players of the case group. The overall mean age of the sample was 18.7±5 years (minimum 14 years and maximum 24 years). Mean age of the participants in the case group was 16.92±2.99 years. The most common injuries reported were ankle joint injuries, followed by knee and hip injuries. Participants of the younger age group (14-19 years old) were found to have a higher risk for lower extremity injures compared to those of the older age group (20-24 years old) (odds ratio [OR], 3.39; 95%CI, 1.15-10.01; p=0.023). Increased true limb length discrepancy was identified among the participants with lower extremity injuries (OR, 4.57, 95%CI, 1.2-17.24; p=0.016) and this discrepancy was strongly associated with ankle injuries (OR, 7.25; 95%CI, 1.85-28.57; p=0.002). There was no significant relationship between lower extremity injuries and gender, limb dominance or Q-angle. CONCLUSIONS: Lower extremity injuries in young badminton players were predominantly located in ankle and knee joints. Younger age and increase in true limb length discrepancy were identified as risk factors for lower extremity injuries in the study sample.